2020
DOI: 10.1038/s41598-020-77385-4
|View full text |Cite
|
Sign up to set email alerts
|

Coastal urbanization alters carbon cycling in Tokyo Bay

Abstract: The carbon budget of Tokyo Bay, a highly urbanized coastal basin, was estimated using a box model that incorporated inorganic and organic carbon data over an annual cycle (2011–2012). The surface water represented net autotrophic system in which the annual net community production (NCP) was 19 × 1010 gC year−1. The annual loading of dissolved inorganic carbon and total organic carbon (TOC) from freshwater inputs was 11.2 × 1010 and 4.9 × 1010 gC year−1, respectively. The annual TOC sedimentation rate was 3.1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…The relationship between the autotrophic condition and the nutrient concentration is consistent with the hypothesized mechanisms related to wastewater treatment (Kubo & Kanda, 2020;Kubo et al, 2017;Kuwae et al, 2016 efficiently than nutrients such as nitrogen and phosphorus (Sedlak, 1991). Through these effluents, the balance of primary production and respiration in the inner bay is offset toward an excess of primary production and the resultant suppression of fCO 2 increase.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The relationship between the autotrophic condition and the nutrient concentration is consistent with the hypothesized mechanisms related to wastewater treatment (Kubo & Kanda, 2020;Kubo et al, 2017;Kuwae et al, 2016 efficiently than nutrients such as nitrogen and phosphorus (Sedlak, 1991). Through these effluents, the balance of primary production and respiration in the inner bay is offset toward an excess of primary production and the resultant suppression of fCO 2 increase.…”
Section: Discussionsupporting
confidence: 79%
“…Although the near‐shore area is generally considered to be a CO 2 source region, some studies have reported that urbanized inner bays in Japan are annual atmospheric CO 2 sinks (Endo et al., 2018; Fujii et al., 2013; Kubo et al., 2017). Especially in Tokyo Bay, CO 2 undersaturation was indicated to be the result of wastewater treatment by continuous measurement of carbonate system (Kubo & Kanda, 2020; Kubo et al., 2017; Kuwae et al., 2016). They suggested that the treatment process removes labile (easily decomposed to inorganic carbon like CO 2 ) carbon, yielding water with relatively less carbon than nutrients, which promotes primary production in the inner bay water.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with post-industrial Japan, the purpose of reclamation projects has changed from farmland to airports and residential buildings (Kitazume, 2012). In the modern society, 95% of the coastline in Tokyo Bay has been transformed from natural to artificial (Atsushi and Jota, 2020). In some developed countries, the transformation of old reclamation areas is now a focus of urban coastal zone development; for example, Spain has also included parts of the reclamation areas in old industrial areas in reconstruction planning (Nogués and Arroyo, 2015).…”
Section: Period From Late Industrialization To Modern Society Eramentioning
confidence: 99%
“…Cultural eutrophication apparently tends to shift this border toward the landside (Kubo et al 2017). In Tokyo Bay, implementation of sewage treatments since the 70's have reduced the loads of biodegradable organic carbon but not the loads of nutrients; as a result, the respiration was reduced but the phytoplanktonic production was favoured, and the Tokyo Bay acts as a strong CO2 sink (Kubo and Kanda 2020). In Guanabara and Tokyo bays, and in Araruama lagoon, the sewage loads are concentrated to well identified regions that emit CO2 to the atmosphere but represent a limited surface area (Cotovicz et al 2015;Kubo et al 2017).…”
Section: Impact Of Eutrophication On the Carbon Cycle Of The Saquarema Lagoonmentioning
confidence: 99%